Sex-Specific Patterns of Cerebral Atrophy and Enlarged Perivascular Spaces in Patients with Cerebral Amyloid Angiopathy and Dementia - Pinho, J.; Almeida, F.C.; Araújo, J.M.; Machado, Á.; Costa, A.S.; Silva, F.; Francisco, A.; Quintas-Neves, M.; Ferreira, C.; Soares-Fernandes, J.P.; Oliveira, T.G. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Cerebral amyloid angiopathy is characterized by amyloid β deposition in leptomeningeal and superficial cortical vessels. Cognitive impairment is common and may occur independent of concomitant Alzheimer disease neuropathology. It is still unknown which neuroimaging findings are associated with dementia in cerebral amyloid angiopathy and whether they are modulated by sex. This study compared MR imaging markers in patients with cerebral amyloid angiopathy with dementia or mild cognitive impairment or who are cognitively unimpaired and explored sex-specific differences.MATERIALS AND METHODS: We studied 58 patients with cerebral amyloid angiopathy selected from the cerebrovascular and memory outpatient clinics. Clinical characteristics were collected from clinical records. Cerebral amyloid angiopathy was diagnosed on MR imaging on the basis of the Boston criteria. Visual rating scores for atrophy and other imaging features were independently assessed by 2 senior neuroradiologists.RESULTS: Medial temporal lobe atrophy was higher for those with cerebral amyloid angiopathy with dementia versus those cognitively unimpaired (P = .015), but not for those with mild cognitive impairment. This effect was mainly driven by higher atrophy in men with dementia, compared with women with and without dementia (P = .034, P = .012; respectively) and with men without dementia (P = .012). Enlarged perivascular spaces in the centrum semiovale were more frequent in women with dementia versus men with and without dementia (P = .021, P = .011; respectively) and women without dementia (P = .011).CONCLUSIONS: Medial temporal lobe atrophy was more prominent in men with dementia, whereas women showed a higher number of enlarged perivascular spaces in the centrum semiovale. Overall, this finding suggests differential pathophysiologic mechanisms with sex-specific neuroimaging patterns in cerebral amyloid angiopathy.Aβamyloid βADAlzheimer diseaseARWMCage-related white matter changesCAAcerebral amyloid angiopathycSScortical superficial siderosisEPVSenlarged perivascular spacesIQRinterquartile rangeMCImild cognitive impairmentMTAmedial temporal lobe atrophy